RISIKO DERAJAT ASFIKSIA NEONATORUM BERDASARKAN JENIS PERSALINAN - Laras Putri Kusumawati; Syiska Atik Maryanti; Muhammad Wildan (Jurnal Keperawatan Terapan, 2019)
Asphyxia neonatorum is the state of the newborn does not immediately breathe spontaneously and regularly. The factor of labor and after delivery is closely related to the asphyxia state. The purpose of this study is to know the risk of degree of asphyxia neonatorum based on the type of labor in Baladhika Husada Hospital of Jember in 2017. The research design using correlational analytics with retrospective design. The sample of this research is some of maternal mothers who gave birth baby asphyxia at Baladhika Husada Hospital of Jember in 2017 with amount of 99 respondents. Secondary data was collected by looking at the history of the type of labor and how many babies had asphyxia on medical record at Baladhika Husada Hospital of Jember in 2017. The data were analyzed by odds ratio formula. The test result using Odds Ratio is known by OR = 3,033, p = 0,064, meaning that the recommended labor has a 3-fold greater risk of causing neonatal asphyxia compared with spontaneous and sectio cesarean delivery. With the results of this study, researchers do not recommend delivery in advance to be the main choice of mother maternity.